Virus Pathogenity of Newcastle Disease in Chicken - Dyah Ayu Hewajuli; N.L.P Indi Dharmayanti (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2011)
Newcastle disease (ND) is one of the highly infectious diseases in poultry industry. Newcastle disease causes high morbidity and mortality in birds, then it causes significant loss for poultry industry. This disease is caused by Avian paramyxovirus-1, included in the genus of Avulavirus and family of Paramyxoviridae. This virus has six prior proteins and two non structural proteins that evolving its genom. Those proteins are Nucleocapsid protein (N), Phosphoprotein (P), Matrix protein (M), Fusion protein (F), Hemagglutinin-neuraminidase protein (HN) and Large polymerase protein (L) and two non structural proteins iVe and W protein which are produced during the transcriptation process of P gen on editing process. Each of the protein has a specific role that responsible for the virulence of the virus. The previous result showed that HN and F proteins have significant contribution in the virulence and spreading of ND virus in the hosts. Virulence of ND virus primarily is determined by the cleavage site of F protein, but the recent research showed that the cleavage site motiv of F0 protein is not the only factor to determine the virulence of ND virus. Besides F protein, other proteins also contribute patern to the virulence of ND virus. ND virus can infect more than 200 species of birds, but the severity level of the disease varies depending on the host and strain of ND virus. Chicken has the highest pathogenicity index compared to other birds. Generally, the immunity system in chicken against infection of ND virus is similar to the immunity system of other birds. Cell mediated and humoral immunity responses play an important role in overcome ND virus. Key words: Newcastle disease, protein, immunity response